A scanning electron microscopic study on the transitional mucosa of the distal colorectal carcinoma - Tun, Ye; Myint, Yi Yi; M. Ansari, Reshma; Md Nor, Azmi (2013)
Colorectal cancer was ranked the most common cancer among males and second most common cancer among females in Peninsular Malaysia (Malaysian cancer statistics, 2006). The transitional mucosa (TM) was apparently normal in histological section but abnormal in mucin histochemistry of large intestinal mucosa immediately adjacent to colorectal adenocarcinoma (Filipe, 1969). The aim of this study was to determine the length of transitional mucosa(cut-off score) in Malaysian with distal colorectal cancer. The distal colon comprises of the descending colon, sigmoid colon and the rectum. The study group included ten normal control patients and ten patients with rectosigmoid tumor. Three samples were taken from each resected rectosigmoid carcinoma specimen( 2, 5, and 10 cms from the proximal margin of the carcinoma). Forty specimen were processed and viewed the mucosal surface under scanning electron microscope(SEM). The mean length of TM was 7.6cm. There was no statistically significant association between age, gender, race, site of tumor, differentiation of tumor and clinical staging with that of the TM changes(pvalue=> 0.05). In conclusion there was longer length of TM changes in this study.